Global and local priming in a multi-modal context - List, Alexandra (Frontiers in Human Neuroscience, 2023)
Perceptual information can be processed at many different scales, from featural details to entire scenes. Attentional selection of different scales has been studied using hierarchical stimuli, with research elucidating a variety of biases in local and global attentional selection (due to, e.g., stimulus properties, brain injury, experience). In this study, the emphasis is on biases produced through recent experience, or level-specific priming effects, which have been demonstrated within both the visual and auditory modalities. Namely, when individuals attend to local information, they are subsequently biased to attend locally (and similarly so with global attention). Here, these level-specific priming effects are investigated in a multi-modal context to determine whether cross-modal interactions occur between visual and auditory modalities during hierarchical processing. Specifically, the study addresses if attentional selection of local or global information in the visual modality subsequently biases auditory attentional selection to that level, and vice versa. Though expected identity priming effects emerged in the study, no cross-modal level-priming effects manifested. Furthermore, the multi-modal context eliminated the well-established within-modality level-specific priming effects. Thus, though the study does reveal a multi-modal effect, paradoxically, the multi-modal context eliminated attentional scope biases within uni-modal transitions. In other words, when visual and auditory information are equally likely require attention, no persistence emerges for processing local or global information over time, even within a single modality.